In-situ strength & constructural assessment of reinforced concrete structures - Tan, Peter Beow Teik. (2009)
In assessment of existing structure, the task is to determine the condition of the structure and its suitability of use. To be able to determine these factors, several aspects of study must be carried out. Of these studies, the major one includes visual inspection, in-situ testing and interpretation of results, design checking and recommendations. Although numerous researches have been carried out, there are still no conclusive and authoritative guidelines in the field of structural assessment. The purpose of this research programme is to provide some findings towards the development of this special field of work. The research programme was set up to study aspects of the reliability of in-situ testing and structural assessment of reinforced concrete structures.